A Curse Dark as Gold - Bunce, Elizabeth C. (New York, NY : Arthur A. Levine Books, 2008)
Upon the death of her father, seventeen-year-old Charlotte struggles to keep the family's woolen mill running in the face of an overwhelming mortgage, but when a man capable of spinning straw into gold appears on the scene she must decide if his help is worth the price.
aAdaptation of the folk tale Rumpelstiltskin.
A Junior Library Guild selection
Keywords: Mills -- Fiction; Uncles -- Fiction; Orphans -- Fiction; Sisters -- Fiction; Ghost stories